The Florida project [videorecording (DVD)] - Baker, Sean, 1971-; Dafoe, Willem; Prince, Brooklynn, 2010-; Vinaite, Bria (Lions Gate Entertainment, 2018)
Language throughout, disturbing behavior, sexual references and some drug material.